UPAYA PENINGKATAN PRESTASI BELAJAR MAHASISWA PADA PERKULIAHAN MOTOR BAKAR MAHASISWA PRODI PTM FKIP UNS MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) - Lanang Pandi Bawono; Ranto Ranto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2025)
This study aims to investigate the application of the Problem Based Learning (PBL) model in improving student learning achievement in the Internal Combustion Engine course for second-semester students of the Mechanical Engineering Education Program, Faculty of Teacher Training and Education, Sebelas Maret University Surakarta, in the 2022 academic year. This research is a classroom action research (CAR) conducted over three cycles, with each cycle consisting of (1) Planning, (2) Implementation, (3) Observation, and (4) Reflection, focusing on actions to improve student learning achievement in the Internal Combustion Engine course. Data collection was carried out using observation methods. The research subjects were students of the Internal Combustion Engine Course, Class A, second semester, of the Mechanical Engineering Education Program, batch 2022, with a total of 42 students. The analysis used in this study is descriptive qualitative analysis. Based on the research results, the application of the Problem Based Learning (PBL) model resulted in an improvement in student learning achievement. The study showed that the students' learning outcomes in the Internal Combustion Engine course in Class A, PTM FKIP UNS, were initially low. The data obtained showed that the percentage of all indicators in the pre-cycle was 69.52%, in the first cycle 96.67%, in the second cycle 72.02%, and in the third cycle 76%. The conclusions drawn from the analysis and discussion of the research are as follows: The application of the Problem Based Learning (PBL) model can improve student learning achievement in the Internal Combustion Engine course in the PTM FKIP UNS, second semester of the 2023 academic year.